Metode Keteladanan Pendidikan Islam dalam Persfektif Quran - Taklimudin, Taklimudin; Saputra, Febri (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2018)
This study aims to understand is how exemplary method Islamic education in the perspective of the Quran, how the exemplary method of Qurani and its implementation in education. This research uses the Research Method Library (library research) with approach method Mudhuiy. That is, by way of collecting all or part of the verses from several letters that relate to the problem of exemplary (Uswah hasanah). So in the end taken a thorough conclusion about the matter according to the view of the Quran. The results of this study indicate that there are several verses of the Quran that are used as the normative basis used as exemplary methods in Islamic education. The normative description explicitly illustrates the exemplary exemplified by the Prophets and the Messenger of Allah. as well as the companions used as a foothold and backrest by practitioners.